Analysis the clothing effect from bleve fireball impact at dynamic parameter - Mazit, Muhammad Asyraf (2019)
This research is conducted to study the effect of BLEVE fireball impact to the human in the area. The research focus on the effect and severity from blast and radiation based on the fabrics they wear. The data used in this is based on the previous case study of tohoku LPG explosion. The experiment starts with determining the relevant theory and equation needed. The parameter of the fireball from the BLEVE is then determined using the formulae for the duration, diameter height and the thermal radiation emitted from the BLEVE fireball. Then, using the quantitative value determined, the effect to the different type of fabrics is simulated using excel worksheet. Among the type of fabrics considered are wool, polyester, acrylic, nylon, etc. It is concluded that the wool is the most resistance material due to its high resistance to heat radiation. Mixture of 65% polyester and 30% cotton, 100% acrylic and 100% nylon are less effective for heat radiation resistance.